CURRENT TREATMENT FOR VENOUS THROMBOSIS - P. S. Laguta («REMEDIUM GROUP» Ltd., 2015)
The term "Venous Thrombosis" (in English literature "Venous Thromboembolism") represents two diseases which are closely related to each other in terms of triggering events and clinical manifestations: lower extremity deep vein thrombosis (DVT) and pulmonary embolism (PE). It is known that PAT (symptomatic or asymptomatic) is discovered in most patients with DVT, and the clinical picture of PAT in most cases reveal (symptomatic or asymptomatic) DVT. Among cardiovascular diseases, venous thrombosis (VT) is ranked 3rd most common in the world with an annual incidence of 100-200 cases per 100,000 population, while fatal PE results in an annual rate of 60 deaths per 100,000 population [1]. It should be borne in mind that these figures are clearly underestimated, given the difficulties of diagnostics and the high incidence of asymptomatic or oligosymptomatic flow of DVT and PE. In addition, the fatal outcome is often the first and only manifestation of PE, and PE firmly holds third place among causes of sudden death [2]. The risk of PE markedly increases with age starting at 40 years old, and this risk double during each subsequent decade of life, and the number of patients with DVT and PE and, probably, deaths from these causes is expected to grow in the future [3].